An Exploratory Study of Differences in Nutrition vs. Non-Nutrition College Students' Attitudes Towards Dietary Protein. (29th May 2020) - Ackerman, Parker; Warren, Cynthia; Miketinas, Derek
Abstract: Objectives: The purpose of this study was to explore differences among nutrition and non-nutrition college students' attitudes towards dietary protein consumption using the Dietary Protein Assessment Questionnaire (DPAQ). Preliminary evidence of the DPAQ demonstrated construct validity and internal consistency. Three factors were retained; factor 1 related to animal versus plant protein sources and their relationship with human and environmental health, factor 2 related to the health of organic protein sources, and factor 3 related to the adequacy of the protein RDA for weight loss and vegetarian diets. Methods: The mean attitude factor scores (factor 1, 2, and 3) were calculated for nutrition and non-nutrition students. The attitude questions included a 5-point Likert scale ranging from "strongly agree " to "strongly disagree." The questionnaire responses were then compared between nutrition and non-nutrition college students using the Mann-Whitney U Test. A p-value of <0.05 was considered statistically significant. Results: Scores differed significantly between nutrition and non-nutrition students for factor 2 (n = 57, median = 5, IQR = 4–6 vs. n = 53, median = 4, IQR = 3–6). There were no significant differences in attitude scores between groups for factor 1 or factor 3. Conclusions: Nutrition students reported more positive attitudes towards conventional protein sources. Nutrition students were more likely to disagree that organic protein sources were healthier than conventional protein sources. Further testing is needed to increase generalizability of these results in order to create effective educational interventions for college students. Funding Sources: None.